Unraveling the Path from Stress to Coping among Indonesian Emerging Adults: The Role of Cognitive Flexibility - Indrasari, Stephanie Yuanita; Suradijono, Sri Hartati; Royanto, Lucia R.M. (UI Scholars Hub, 2026)
Abstract Emerging adulthood (ages 18-25) is a developmental stage marked by significant life transitions, which can heighten stress levels. In Indonesia, urban dynamics and socio-cultural pressures further intensify this stress among emerging adults. Cognitive flexibility, the ability to adaptively shift thoughts and strategies in response to changing circumstances, is an important factor in effective coping. This study examined the relationships among stress and adaptive coping, with cognitive flexibility playing a role as a mediator, among Indonesian emerging adults over three months (Time 1: N = 512; Time 2: N = 166) using a two-wave cross-lagged panel model (CLPM). Results indicated that cognitive flexibility did not mediate the relationship between stress and adaptive coping. Although stress was not directly related to adaptive coping, it was negatively associated with cognitive flexibility. In turn, cognitive flexibility was positively related to adaptive coping. These findings highlight cognitive flexibility as an independent adaptive resource. Future research should incorporate it into academic and counseling programs, helping individuals better navigate complex and emotionally challenging situations.